Green building illustrated - Ching, Francis D. K. 1943-; Shapiro, Ian M.
"In Francis D.K. Ching's signature style, this fully illustrated guide to the theory and practice of green building offers practicing professionals and students a framework and detailed strategies for designing substantively green buildings. This guide explains why we need to build green, the theories behind green building, and advancements in the industry--with a focus on sustainable sites, approaching net-zero energy, low water usage, minimum-impact materials and superior indoor environmental quality. Updates to this edition include: all-new case studies featuring buildings with proven zero enery performance; expanded guidance for the schematic design of high-performance buildings; strategies for affordability in green design and construction; and expanded coverage of complex green building topics, such as heating system and hot water selection, building envelopes, and integrating renewable energy. This updated edition aligns with the latest codes and standards, including: IgCC-ASHRAE 189, IBC, LEED, BREEAM, Green Globes, Passivhaus, Living Building Challenge, WELL and more"--Provided by publisher.